Hindsight Graduate History Journal Vol. 1 (California State University, Fresno. College of Social Sciences. Department of History)
Published both hard-copy and digitally from 2007 to 2012, Hindsight provided an outlet for graduate students in the social sciences, arts and humanities to gain experience in professional writing and promote their work within the academic community. The journal is dedicated to the publication of interdisciplinary historical work submitted by graduate students from the social sciences, arts and humanities, and is an academic journal run by graduate students, for graduate students.